Optimal provision of public goods: a synthesis - Claus Thustrup Kreiner; Nicolaj Verdelin (Center for Economic Studies and ifo Institute (CESifo), 2009)
There currently exist two competing approaches in the literature on the optimal provision of public goods. The standard approach highlights the importance of distortionary taxation and distributional concerns. The new approach neutralizes distributional concerns by adjusting the non-linear income tax, and finds that this reinvigorates the simple Samuelson rule when preferences are separable in goods and leisure. We provide a synthesis by demonstrating that both approaches derive from the same basic formula. We further develop the new approach by deriving a general, intuitive formula for the optimal level of a public good without imposing strong assumptions on preferences. This formula shows that distortionary taxation may have a role to play as in the standard approach. However, the main determinants of optimal provision are completely different and the traditional formula with its emphasis on MCF only obtains in a very special case.
Keywords: H41; H23; H11; 330; Public good provision; distortionary taxation; distribution; Öffentliches Gut; Kosten-Nutzen-Analyse; Soziale Wohlfahrtsfunktion; Optimale Besteuerung; Theorie